Emergence From General Anesthesia and Evolution of Delirium Signs in the Post-Anesthesia Care Unit. Issue 2 (April 2016) - Card, E.; Panharipande, P.; Tomes, C.; Lee, C.; Wood, J.; Nelson, D.; Graves, A.; Shintani, A.; Ely, E. W.; Hughes, C.
Abstract : Surv Anesthesiol 2016;60(2):75–76 Delirium is a common occurrence; 60% to 80% of mechanically ventilated patients and 20% to 50% of patients with lower severity illness develop delirium while in the hospital. It has been suggested that delirium in the postanesthesia care unit (PACU) is predictive of worsened outcome.